Intoxicação experimental por Niedenzuella stannea (Malpighiaceae) em bovinos e correspondente detecção de Monofluoracetato - Arruda, Felipe Peixoto de (2016)
In Brazil monofluoroacetate containing plants are represented by 11 species that belong to three principle genera: Palicourea (Rubiaceae), Amorimia (Malpighiaceae), and Tanaecium (Bignoniaceae). These plants can cause acute cardiac failure often referred to as sudden death syndrome. The objective of this paper was to determine if Niedenzuella stannea (Malpighiaceae) contained the toxin monofluoroacetate that is responsible for sudden death syndrome and to report the clinical signs and pathology in cattle associated with experimental poisoning by it. Monofluoroacetate was detected in all plant parts except mature leaves. Niedenzuella stannea was dosed to cattle. The clinical signs and pathology observed were similar to those reported by other MFA-containing plants. In summary, this is the first report that N. stannea contains monofluoroacetate and causes sudden death in cattle